2005
DOI: 10.1111/j.1365-2109.2005.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation diet based on fatty acid content for male Penaeus monodon (Fabricius) broodstock

Abstract: The contents of three essential fatty acids, arachidonic acid (AA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), from wild Penaeus monodon broodstock were evaluated in comparison with natural diet fed P. monodon. Spermatophores of wild male broodstock contained higher levels of AA than those of arti¢cial diet fed males. Polychaetes had higher proportion of AA to EPA and DHA at 5.8:5.5:1 in mud polychaetes followed by 12:7:1 in sand polychaetes, while DHAwas a preferential n-3 highly unsaturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
89
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 33 publications
5
89
0
8
Order By: Relevance
“…Because it is a precursor to steroid hormones and comprises a large proportion of the lipid in crustacean eggs and because they cannot synthesize it or substantially replace it with other dietary sterols (Harrison 1990), it is likely that maturing broodstock would require greater levels than immature shrimp. Compared with levels of 0.3-0.4% recommended for diets of nonmaturing shrimp (Akiyama & Dominy 1989) and inclusion levels ranging from 0.25 to 0.5% in maturation diets for P. vannamei (Cahu et al 1994) and P. monodon (Meunpol et al 2005) respectively, the levels found in P. helleri in the present study (5-10 g kg À1 of DM) appear adequate. This was up to twice the cholesterol levels reported for cultured P. nuntia in Thailand (3-5 g kg À1 of DM: Limsuwatthanathamrong et al 2012).…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…Because it is a precursor to steroid hormones and comprises a large proportion of the lipid in crustacean eggs and because they cannot synthesize it or substantially replace it with other dietary sterols (Harrison 1990), it is likely that maturing broodstock would require greater levels than immature shrimp. Compared with levels of 0.3-0.4% recommended for diets of nonmaturing shrimp (Akiyama & Dominy 1989) and inclusion levels ranging from 0.25 to 0.5% in maturation diets for P. vannamei (Cahu et al 1994) and P. monodon (Meunpol et al 2005) respectively, the levels found in P. helleri in the present study (5-10 g kg À1 of DM) appear adequate. This was up to twice the cholesterol levels reported for cultured P. nuntia in Thailand (3-5 g kg À1 of DM: Limsuwatthanathamrong et al 2012).…”
mentioning
confidence: 78%
“…This was similar to the lipid levels reported for Perinereis sp. by Meunpol et al (2005) ) were lower than levels found by Brown et al (2011) in N. virens (130-170 g kg…”
mentioning
confidence: 87%
See 3 more Smart Citations